An Experimental Economic Analysis of Banker Behavior - Hülsen, Martin (Schriften zum europäischen Management, 2018)
Martin Hülsen explores individual behavioral trustworthiness of and within the banking industry in Germany based on an economic experiment combined with psychological instruments. He finds that bankers have a reputation for being untrustworthy. However, his evidence also shows that the true story of banker trustworthiness is more complex: In particular, he explores differences between employees of commercial banks on the one hand and employees of savings and cooperative banks on the other. The Contents Reviews of the German banking industry and the economics of other-regarding behavior Experiment exploring behavioral trustworthiness of bankers Target Groups Researchers and students of behavioral and experimental economics and banking systems Experts in organizational culture and compliance in banks The Author Martin Hülsen studied Business Administration at Frankfurt School of Finance & Management and Managerial and Financial Economics at HEC Paris. He completed his doctoral thesis under the supervision of Prof. Dr. Marcel Tyrell at Zeppelin University, Friedrichshafen. He works as a project manager for a leading global consultancy firm and has specialized in the financial services industry. .